Tekstualitas dan Kontekstualitas Metodologi Baca Tulis Al-Qurâ€™Än (BTQ): Studi Teks, Bahasa dan Sejarah - Zainuddin, Ammar (Atthulab: Islamic Religion Teaching and Learning Journal, 2021)
Abstract: This article aims to examine the learning textbook for reading and writing al-Qur'Än at the primary level from the perspective of teaching foreign languages. Because this study focuses on books on the method of learning to read and write al-Qur'Än, the text study is the methodological choice in this research. Apart from language, the writer also uses history in this study as a material for discussion and concluding. The results of this study indicate that the books or methods of reading and writing al-Qur'Än are not final, especially in teaching Arabic phonetics for speakers of Indonesian (non-Native Speak Arabic). The final review of this paper implies that there is a difference in the concept of learning methodology for reading and writing al-Qur'Än between memorizing, reading and writing hijaiyyah letters. On a large scale, the compilers of the book needed to re-develop the tarÄ«b of these letters. While on a small scale, it is enough for teachers or educators to modify the tarÄ«b in the form of demonstrations and the like. Â  Abstrak: Artikel ini bertujuan untuk menelaah buku teks pembelajaran baca tulis al-Qurâ€™Än pada tingkat dasar dengan perspektif pengajaran bahasa asing. Penelitian ini menggunakan metodologi studi teks yang ditunjang dengan pendekatan sejarah dan bahasa sebagai bahan diskusi dan penarik kesimpulan. Hasil dari penelitian ini menyatakan bahwa metode yang digunakan dalam buku-buku pembelajaran Baca Tulis al-Qurâ€™an (BTQ) belumlah final.khususnya dalam pengajaran fonetik Arab bagi penutur Bahasa Indonesia (non-Native Speak Arabic). Implikasi dari ulasan akhir tulisan ini ialah adanya perbedaan konsep metodologi pembelajaran Baca Tulis al-Qurâ€™Än antara menghafal, membaca dan menulis huruf hijaiyyah. Dalam skala besar para penyusun buku perlu untuk mengembangkan kembali tarÄ«b huruf-huruf tersebut. Sedangkan dalam skala kecil, cukup para guru atau pendidik yang memodifikasi tarÄ«b tersebut dalam bentuk peraga dan semisalnya.